Perbaikan Tata letak Departemen Penataan Individual Quick Freezing dengan Menggunakan Studi Waktu. Studi Kasus di PT. Inti Luhur Fuja Abadi Pasuruan - Aseanto, Budi Tri; Maryani, E.F. Sri; Hidayat, Nur (Jurnal Teknologi Pertanian, 2004)
Fish industry is one of the most strategic industry in Indonesia, this fact supported by the geographic location that caused plentiful materials available for this industry. Freezing is the well know way to keep the fresh quality of the materials, specifically for food materials. One kind of frozen product in fish industry is WGGS (Whole Gilled Gutted and Scaled) croacker frozen fish, were croacker fish that had been gilled, gutted and scaled during the production process. The problem find in the production of WGGS croacker frozen fish in Inti Luhur Fuja Abadi factory is the unbalanced flow of materials between the washing department with the capacity of the IQF (Individual Quick Freezing) pan ordering department. From the early measure to the cycle time at IQF pan ordering department, identified that too long transportation activity did by the workers caused longer cycle time. Longer cycle time caused longer standard time, and longer time standard effect to lower capacity of the department. To minimized the cycle time at IQF pan ordering department, also to reducing the transportation line, time study is one alternative to identified which move or work methodâs elements use longer time compared with others. After the unefficient move or work methodâs elements found, redesign plannig for the departmentâs layout held by using load distanceâs score table. Key words: IQF pan ordering department, cycle time, standard time, redesign, load distanceâs score table.